A Review on Natural Fiber Bio-Composites, Surface Modifications and Applications - Zwawi, Mohammed (Molecules (Basel, Switzerland), 2021)
Increased environmental concerns and global warming have diverted focus from eco-friendly bio-composites. Naturals fibers are abundant and have low harvesting costs with adequate mechanical properties. Hazards of synthetic fibers, recycling issues, and toxic byproducts are the main driving factors in the research and development of bio-composites. Bio-composites are degradable, renewable, non-abrasive, and non-toxic, with comparable properties to those of synthetic fiber composites and used in many applications in various fields. A detailed analysis is carried out in this review paper to discuss developments in bio-composites. The review covers structure, morphology, and modifications of fiber, mechanical properties, degradable matrix materials, applications, and limitations of bio-composites. Some of the key sectors employing bio-composites are the construction, automobile, and packaging industries. Furthermore, bio-composites are used in the field of medicine and cosmetics.